CDS - Stock Market Chaotic Relationship - Turkish Stock Market Case - Bildirici, Melike; Sonustun, Bahri; Gokmenoglu, Seyit M. (AMER INST PHYSICS, 2019)
In this paper, two important points will be investigated, if the variables have the chaotic behavior by LLE and Henon map and if they have chaotic causality by Hristu-Varsakelis and Kyrtsou causality test. It was determined the chaotic behavior of the Turkish stock market and CDS. We found the evidence of bi-directional causality between CDS and Bist-100.
Keywords: TRANSMISSION; Physics